Simulation based energy and resource efficient casting process chain selection: a case study - Salonitis, Konstantinos; Jolly, Mark R.; Zeng, Binxu (Elsevier, 2017)
Casting processes are among the most energy intensive manufacturing processes. A typical modern casting process contains different stages, classified as melting-alloying, moulding, pouring, solidification, fettling, machining and finishing respectively. At each stage, large amounts of energy are consumed. Since a number of different casting processes exist, it is not always straightforward which process chain to select among the available ones. Up to now the selection is based on cost criteria. This paper focuses on the different criteria that needs to be considered and how they can be simulated focusing especially on the energy and resource efficiency of casting stages. A disruptive technology that uses a rapid induction furnace to melt just enough metal for a single mould rather than bulk melting used in traditional processing is proposed and validated.
Keywords: Casting; Simulation; Energy efficiency